Firm Size Moderates the Effect of Free Cash Flow, Firm Growth, and Profitability on Debt Policy (Jurnal Dinamika Akuntansi, 2019)
The purpose of this research is to describe the effect of free cash flow, firm growth, and profitability on debt policy by firm size as a moderating variable. The population in this study was 144 manufacturing companies sector that listed on the Indonesia Stock Exchange (IDX) during the years 2014-2016. The sample selection used purposive sampling method that generates as much as 61 samples of companies. This research used secondary data taken from annual reports. Testing of this research was done by using regression analysis with the difference absolute value test by IBM SPSS 21 version. The result of this research showed that free cash flow does not have significant effect on debt policy, while firm growth and profitability have significant effect on debt policy. Firm size is able to moderate the effect of firm growth and profitability on debt policy, but not able to moderate the effect of free cash flow on debt policy. The conclusion of this research is that firm size can affect on company’s judgment in deciding the debt policy taken to fund its operations and investment activities.